Measuring Social Impact of The Minhati Scholarship Program: An SROI-Based Evaluation of ZISWAF Fund Distribution at LAZISWAF UNIDA Gontor - Wibisono, Vina Fithriana; Zahro', Khurun'in; Jakiyudin, Ahmad Havid; Rafifah, Fairuz Hasna (Journal of Islamic Economic Laws, 2025)
LAZISWAF UNIDA Gontor is a progressive ZISWAF waqf institution that supports education through its flagship program, Minhati, which provides scholarships for underprivileged students. Despite the continuous distribution of ZISWAF funds, there has been no comprehensive measurement of the program’s actual impact on its beneficiaries. This raises a critical issue regarding the effectiveness, transparency, and accountability of ZISWAF fund utilization in achieving social and educational outcomes. This study aims to evaluate the effectiveness of the Minhati program by measuring the social value it creates using the Social Return on Investment (SROI) approach. The research method used is qualitative with the SROI approach to assess the program’s social, economic, and environmental impact. Primary data is sourced from the 2023-2024 annual financial report, and data collection involves questionnaires from 29 scholarship recipients by purposive sampling. The results of this study indicate that the SROI value is 1,67, indicating that every Rp 1 invested generates Rp 1.67 in social impact. This demonstrates that the Minhati program significantly enhances students' welfare, benefits their families, and contributes to social and religious affairs.